Influencia de la desinfeccion posordeño con lugol sobre la concentracion de iodo en leche de vacas - Ramirez, R.=700 1 Colome, H.
(Es, En)
Ilus., 10 ref.
Keywords: MASTITIS BOVINA; VACA; GANADO BOVINO; DESINFECCION; GLANDULAS MAMARIAS; YODO; CUBA; YODO EN LECHE; LUGOL